(untitled) (CIPEEX, 2022)
THE PRESENT STUDY AIMED TO VERIFY THROUGH EXPERIMENTAL STUDIES, TO INVESTIGATE THE VARIABLES THAT INFLUENCE THE REAPPEARANCE OF BEHAVIORS. RESURGENCE IS CHARACTERIZED AS A PHENOMENON IN WHICH A GIVEN SITUATION, BEHAVIORS THAT WERE STRENGTHENED IN PAST EVENTS AND SUBSEQUENTLY DO NOT PRODUCE CONSEQUENCES. IN A FUTURE SITUATION, IN WHICH CURRENT CONTINGENCIES ARE SIMILAR, SUCH BEHAVIORS TEND TO REAPPEAR. A COMPUTATIONAL PROGRAM WAS DEVELOPED, BASED ON ANIMAL STUDIES DEVELOPED BY EPSTEIN AND SKINNER (1980), AND ADAPTED FOR THE COMPUTATIONAL PLATFORM. PARTICIPATED IN THE STUDY 8 VOLUNTEERS, UNIVERSITY STUDENTS WHO WERE EXPOSED TO THREE DIFFERENT EVENTS WHERE THEY HAD TO RESPOND TO INSTRUCTIONS AND TOUCH THE COMPUTER SCREEN WHERE THERE WERE THREE POSSIBILITIES OF RESPONSES WHICH WERE REINFORCED ACCORDING TO THE ALLOCATION BASED ON COST PER NUMBER OF RESPONSES (1, 4 AND 10). THE DESIGN DESCRIBED IN PHASES WAS: BASELINE 1 (B1), TRAINING 1 (T1), TRAINING 2 (T2), BASELINE 2 (B2), CONSISTED OF REINFORCING A CERTAIN CONTINGENCY IN FORCE, WHICH WAS LATER PUT INTO EXTINCTION , THEN IN ANOTHER CONTINGENCY, THERE WAS THE POSSIBILITY THAT THE EXTINCT RESPONSES WOULD BE REINFORCED AGAIN. THE RESULTS SHOWED THAT RESURGENCE IS A PHENOMENON THAT OCCURRED IN PHASES B2, INDEPENDENT OF CONTINGENCY COST, PROVING THAT NEW CONTINGENCIES OF REINFORCEMENT THAT CEASED TO OPERATE IN THE PAST, ACT IN THE OCCURRENCE OF REPERTOIRES SIMILAR TO THOSE THAT WERE REINFORCED IN A PREVIOUS SITUATION.